Post-Pandemic Drivers of E-Wallet Continued Use: Cross-Regional Evidence from Southeast Asia and Sub-Saharan Africa - Surbakti, Lidya Primta; Kabir, Muhammad Auwal; Swatdikun, Trairong; Wibawaningsih, Ekawati Jati; Maulana, Agus (Universitas Pendidikan Indonesia, 2025)
This study assesses and compares the factors that shape the ongoing use of e-wallets in Indonesia and Nigeria after the coronavirus pandemic. Data were collected through an online survey of 275 respondents in both countries. Partial least squares structural equation modeling (PLS SEM) was applied, revealing that perceived risk and perceived ease of use significantly influenced continued e-wallet use in both Indonesia and Nigeria, but awareness and social influence did not. Perceived usefulness also had a weak but significant effect on ongoing use. The analysis did not confirm that educational level moderated the indirect links among variables, except for the link between awareness and continuous use in Nigeria. Consequently, the study suggests that e-wallet providers in Indonesia should promote acceptance via social networks, while in Nigeria they should increase orientation and awareness for those lacking formal education to encourage post pandemic use.